The Effect of Anchovy Stolephorus baganensis on Salivary Mutans Streptococci - Harun Agunawan; Soeherwin Mangundjaja (Fakultas Kedokteran Gigi, Universitas Gadjah Mada, 2010)
A clinical trial was carried out to investigate the effect of Anchovy of Stolephorus baganensis on mutans streptococci inhibiting the growth of the salivary mutans streptococci for a period of one week consumption.Before enrolled in the study, respondents filled out and signed the informed consent. Twenty respondents participated as the subjects on the clinical trial, conducting two times of treatment as follows: twenty astreatment groups before and after consuming anchovy of Stolephorus baganensis and the twenty subjects as control groups before and after consuming non-anchovy of Stolephorus baganensis. Saliva samples werecollected before and after consuming anchovy of Stolephorus baganensis and with a non-anchovy of Stolephorus baganensis. A serial dilution was made, followed by inoculating on TYS20B medium). Data which were obtained from colony forming units of salivary mutans streptococci grew on the TYS20B medium before and after consuming anchovy of Stolephorus baganensis were analyzed in a descriptive and “t” test.Results showed that there was no significance in the average amount of Streptococcus mutans colonies between before and after consuming non-anchovy of Stolephorus baganensis. However, a significant difference wasfound respectively as results before and after consuming anchovy of Stolephorus baganensis. We concluded that Anchovy of Stolephorus baganensis has antimicrobial activity against local strains of Streptococcus mutans isolated from human harboring species. Therefore in a long term of consuming Anchovy fish of Stolephorus baganensis, caries can be prevented.